Psychometric properties of the Iranian version of the Anxiety Sensitivity Index-3 (ASI-3) - Foroughi, Ali Akbar; Mohammadpour, Mohsen; Khanjani, Sajad; Pouyanfard, Sahar; Dorouie, Nadia; Parvizi Fard, Ali Akbar (Trends in psychiatry and psychotherapy, 2019)
Abstract Introduction: Anxiety sensitivity plays a prominent role in the etiology of anxiety disorders. This construct has attracted widespread interest from experts and researchers. The Anxiety Sensitivity Index (ASI-3) is the most common scale for measuring anxiety sensitivity. Objective: To analyze the psychometric properties and factor structure of the ASI-3 in Iranian student samples. Methods: 220 students (135 women, 85 men) from Kermanshah University of Medical Sciences were selected by the convenience sampling method to evaluate the psychometric properties and analyze the factor structure of the ASI-3. The subjects were also asked to complete the Acceptance and Action Questionnaire-II (AAQ-II), Whiteley Index, Intolerance of Uncertainty, and Neuroticism scales. LISREL and SPSS were used to analyze the data. Cronbach's alpha and correlation coefficients were calculated and confirmatory factor analysis was conducted. Results: The results of the confirmatory factor analysis revealed a three-factor structure with physical, cognitive, and social components (comparative fit index = 0.94; normed fit index = 0.91; root mean square error of approximation = 0.09). The ASI-3 had positive and significant correlations with health anxiety (0.59), intolerance of uncertainty (0.29), and neuroticism (0.51). Furthermore, the ASI-3 had a negative and significant correlation with the AAQII (-0.58). Cronbach's alpha coefficients for the whole scale and for the physical, cognitive, and social concerns factors were 0.90, 0.74, 0.79, and 0.78, respectively. The invariance of the index was significant compared to the original English version. Conclusion: In general, the results support the adequacy of the psychometric properties of the Persian version of the ASI-3. Theoretical and applied implications will be discussed. Resumo Introdução: A sensibilidade à ansiedade desempenha um papel proeminente na etiologia dos transtornos de ansiedade. Esse construto tem atraído grande interesse entre especialistas e pesquisadores. O Anxiety Sensitivity Index (ASI-3; em português, Escala de Sensibilidade à Ansiedade) é a medida mais utilizada para medir sensibilidade à ansiedade. Objetivo: Analisar as propriedades psicométricas e a estrutura fatorial do ASI-3 em estudantes iranianos. Métodos: Para avaliar as propriedades psicométricas e analisar a estrutura fatorial do ASI-3, 220 estudantes (135 mulheres, 85 homens) da Kermanshah University of Medical Sciences, Irã, foram selecionados via amostragem por conveniência. Eles foram solicitados a completar os seguintes instrumentos: Acceptance and Action Questionnaire-II (AAQ-II), Whiteley Index, Intolerance of Uncertainty e Neuroticism. Os programas LISREL e SPSS foram utilizados para analisar os dados. Alfa de Cronbach e coeficientes de correlação foram calculados, e foi realizada análise fatorial confirmatória. Resultados: Os resultados da análise fatorial confirmatória revelaram uma estrutura de três fatores, incluindo componentes físicos, cognitivos e sociais [comparative fit index (CFI) = 0,94; normed fit index (NFI) = 0,91; root mean square error of approximation (RMSEA) = 0,09]. O ASI-3 demonstrou correlações positivas e significativas com ansiedade em relação à saúde (0,59), intolerância à incerteza (0,29) e neuroticismo (0,51). Além disso, o ASI-3 teve uma correlação negativa e significativa com o AAQII (-0,58). Os coeficientes alfa de Cronbach para toda a escala e para os fatores preocupação física, cognitiva e social foram 0,90, 0,74, 0,79 e 0,78, respectivamente. A invariância do índice foi significativa em relação à versão original. Conclusão: Em geral, os resultados sugerem que as propriedades psicométricas da versão persa do ASI-3 são adequadas. Implicações teóricas e práticas serão discutidas.